RECONSTRUCTING SITA’S IMAGE: A PSYCHOLOGICAL APPROACH TO VAYU NAIDU’S SITA’S ASCENT - Gautam, Subah (International Journal of Psychosocial Rehabilitation, 2020)
The paper is an attempt to study Sita’s psychological aspect through her interaction with other characters from the epic Ramayana as portrayed in Vayu Naidu’s Sita’s Ascent, which is a collection of narratives based on the Ramayana. It ascertains that women suffer because of male dominance and it tries to depict the psychological turmoil of female characters during their suffering, which eventually leads them to form varied perspectives. The paper focuses on a number of questions that awake Sita’s conscience in Sita Ascent, such as; does she have some identity of her own? Do males in the Ramayana consider her interests? Why is she treated as the source of objectification? Is it necessary to sacrifice her wishes for the sake of Pativratyam dharma or the sake of motherhood? Why is she always being enquired to prove her chastity based on suspicion? Moreover, why is she believed to be inferior and fragile? Answers to these questions would be presented to comprehend Sita’s psyche and the gender injustice, which is being realized in the story of the Ramayana.